Faktor – Faktor Komunikasi Bisnis Terhadap Pembentukan Karakter Kewirausahaan Mahasiswa Aktif Ilmu Komunikasi Universitas Negeri Jakarta - Dhesvina, Rizka Humaira; Sutjipto, Vera Wijayanti; Putri, Elisabeth Nugrahaeni (LUGAS Jurnal Komunikasi, 2024)
Entrepreneurship plays a crucial role in enhancing a country's welfare. Toachieve success in this field, it is essential to foster strong businesscommunication skills that facilitate collaboration among entrepreneurs.Business communication is a key factor in establishing effectivepartnerships through various applications. This study aims to identify thefactors that most significantly influence business communication inshaping the entrepreneurial character of active Communication Sciencestudents at Jakarta State University. The research is based on theintegrated theories of Bakke and Argyris. A quantitative approach isemployed, using both descriptive and causal study methods. The researchdesign is explanatory. The findings indicate a positive and significantimpact, with an R-squared value of 0.839, or 83.9%. This suggests thatbusiness communication plays a vital role in developing entrepreneurialcharacter among students, ultimately contributing to the emergence ofmore capable young entrepreneurs in the future.